Probióticos e betalaínas: avanços em co-encapsulação e aplicação em bebida funcional - Deus, Cassandra de (2024)
The combination of bioactive ingredients in a single system offers unique opportunities to enhance health benefits, such as promoting the balance of the intestinal microbiota and protecting against conditions related to oxidative stress and cellular inflammation. In this context, the co-encapsulation of probiotics (Lacticaseibacillus rhamnosus) and betalain extract, using spray drying technology, was explored as an innovative strategy for application in a non-dairy functional drink. The study investigated encapsulation efficiency, probiotic viability throughout storage, and the resistance of the co-encapsulates under conditions that simulate the gastrointestinal environment. The microparticles were then applied to kombucha, demonstrating the stability and functionality of the compounds during 60 days of storage. The results showed that co-encapsulation effectively protected the probiotics against adverse conditions, ensuring their release in the colonic phase. The betalain extract showed safety in cytotoxicity tests against Caenorhabditis elegans. The application in kombucha validated the technological and commercial viability of the proposal, preserving the survival of the probiotics and contributing a greater nutritional appeal to the drink. This work contributes to the advancement of functional food technologies, meeting the growing demand for healthy and innovative products with potential application in different food matrices, helping to fill the existing gap in the market for probiotic products enriched with microparticles.